Experimental evaluation of using calcein and alizarin red S for immersion marking of bighead carp Aristichthys nobilis (Richardson, 1845) to assess growth and identification of marks in otoliths, scales and fin rays. (31st March 2015) - Lü, H.‐J.; Fu, M.; Xi, D.; Yao, W.‐Z.; Su, S.‐Q.; Wu, Z.‐L.
Summary In order to evaluate the effects of immersion marking with calcein (CAL) and alizarin red S (ARS) on growth and mortality of juvenile bighead carp Aristichthys nobilis, and assess mark quality in otoliths, scales, and fin rays, CAL from 50 to 200 mg L−1 and ARS from 150 to 300 mg L−1 concentrations were used. With the exception of non‐lateral line scales from 50 mg L−1 CAL treatments, immersion for 24 h produced detectable marks in sagittae, lateral line and non‐lateral line scales, and fin rays (dorsal, pectoral, ventral, anal, and caudal) at 100 days post‐marking. Detectable fluorescent marks in sagittae were readily observed at concentrations of 150–200 mg L−1 CAL or 150–300 mg L−1 ARS. Marks were poorly visible in all non‐lateral line scales from both CAL‐ and ARS‐treated groups. Fluorescent marks were readily detected in lateral line scales at 100–200 mg L−1 CAL or 150–300 mg L−1 ARS, and in fin rays at 150–200 mg L−1 CAL or 150–300 mg L−1 ARS. In particular, optimal marks were observed at the highest concentrations investigated in sagittae (300 mg L−1 ARS), lateral line scales (150–200 mg L−1 CAL or 250–300 mg L−1 ARS), and fin rays (200 mg L−1 CAL or 250–300 mg L−1 ARS). However, fluorescent marks visible to the naked eye were not produced by any of the CAL or ARS treatments in sagittae, scales, or fin rays during this experiment. In addition, there was no significant difference on survival and growth of marked fish compared to controls throughout the experiment (P > 0.05).